PENGEMBANGAN POCKET BOOK DIGITAL BERBASIS ETNOSAINS SAPI SONOK MADURA UNTUK MENINGKATKAN LITERASI SAINS SISWA PADA MATERI KLASIFIKASI MAKHLUK HIDUP - Elisa Indah Mayang Sari; Mochammad Yasir; Nur Qomaria; Rahmad Fajar Sidik; Siti Eneng Sururiyatul Muâ€™aziyah (Bioedukasi Jurnal Pendidikan Biologi, 2026)
This study aims to determine the validity, readability, student response, and improvement of students' science literacy towards digital Pocket book. Subject matter used is the classification of living things. This study is a type of R&D research with the ADDIE development model. The subjects of this study were 26 students of class VII-G of SMPN 5 Pamekasan. Based on the results of the study, it can be concluded that: (1) The digital Pocket book based on ethnoscience of Madura Sonok Cattle obtained a validity percentage value from material experts and media experts of 89.06% and 93.06% with very valid criteria. (2) The readability aspect based on the student questionnaire obtained an average score of 90.82% with a very good category (3) The response aspect based on the student questionnaire obtained an average score of 92.26% with a very good category (4) The increase in student science literacy based on the N-gain score was 0.62 with moderate criteria, so that the digital Pocket book based on the ethnoscience of Madura Sonok Cattle can improve students' science literacy. The conclusion of the study shows that the digital Pocket book based on the ethnoscience of Madura Sonok Cattle produced is very valid for use as a science teaching material and can improve students' science literacy.Â Kata kunci: Pocket book digital, literasi sains, sapi sonok, klasifikasi makhluk hidup